Impact of the NREGS on Children's Intellectual Human Capital - Mani, Subha (The journal of development studies, 2020)
This paper uses panel data from the Young Lives Survey to examine the effect of the world's largest public works program and India's flagship social protection program, the National Rural Employment Guarantee Scheme (NREGS), on children's learning outcomes such as grade progression, reading comprehension test scores, writing test scores, math test scores, and Peabody Picture Vocabulary Test (PPVT) scores. We find that the program has strong positive effects on these outcomes in both the short-and-medium run. Finally, the impact estimates reported here are robust to a number of econometric concerns such as -program placement, selective attrition, and type I error